Proposição de metodologia em suporte à avaliação do impacto do uso e ocupação do solo na desconformidade da qualidade da água em pequenas e microbacias hidrográficas rurais - Silva, Felipe Andrade (2018)
There are many uses and form of occupation of land observed in river basins. Especially in rural small and micro watershed (PMBH rural), these are shown as the main responsible for changes in water quantity and quality available to communities. Legislation such as CONAMA Resolution No. 357/05 are responsible for establishing water quality standards for water bodies, depending on the different water uses. When the water bodies present inferior quality to the demand for the uses that are given to the water is characterized the scenario of nonconformity, that brings great risks to the users. It is important for rural PMBHs to evaluate the impacts of land–use and land–occupation in the occurrence of nonconformity scenarios. In the context of these studies, the literature points to the need to evaluate which methodologies are best suited to the use in this management scale. Multicriteria analysis tools then emerge as an alternative to verify this adequacy. Based on the use of multicriteria analysis tools, a methodology was proposed to assist in the selection of a method to evaluate the impact of land–use and land–occupation on the water quality to be used in rural PMBH. The proposal evaluates 8 methodological alternatives on the optics of 6 analysis criteria and presents 3 stages for its application, being 'Diagnostic', 'Multicriteria Analysis' and 'Recommendation'. Throughout its development the proposal has gone through 3 stages of evaluation. These contributed to the elaboration of a revised final version and to the definition of the guidelines for its correct application. The proposal developed was considered by representatives of the water resource management body of Espírito Santo state and representatives of 3 river basin committees as easy to understand and as having potential of practical application.